2015
DOI: 10.1120/jacmp.v16i5.5612
|View full text |Cite
|
Sign up to set email alerts
|

High‐density dental implants and radiotherapy planning: evaluation of effects on dose distribution using pencil beam convolution algorithm and Monte Carlo method

Abstract: High atomic number and density of dental implants leads to major problems at providing an accurate dose distribution in radiotherapy and contouring tumors and organs caused by the artifact in head and neck tumors. The limits and deficiencies of the algorithms using in the treatment planning systems can lead to large errors in dose calculation, and this may adversely affect the patient's treatment. In the present study, four commercial dental implants were used: pure titanium, titanium alloy (Ti‐6Al‐4V), amalga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…8 The algorithms used for dose calculations in treatment planning systems (TPS) cannot accurately calculate the scattered dose. 9 The Monte Carlo (MC) simulation is the best way to model the radiation beam and its interactions. More accurate results are obtained in dose calculations using MC simulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 The algorithms used for dose calculations in treatment planning systems (TPS) cannot accurately calculate the scattered dose. 9 The Monte Carlo (MC) simulation is the best way to model the radiation beam and its interactions. More accurate results are obtained in dose calculations using MC simulation.…”
mentioning
confidence: 99%
“…More accurate results are obtained in dose calculations using MC simulation. 1,5,9 Several groups have made measurements to investigate dental implant materials effect on the dose distribution. Ozen et al 8 and Beyzadeoglu et al 10 evaluated dose increment related to scattered radiation from bone-dental implant surface and beam incidence angle.…”
mentioning
confidence: 99%
“…Possible reasons for the noted disagreement between the measured and calculated doses include a large dose gradient present in oral cavity, a dose variation from positioning uncertainties of the dosimeters, radiation scattering caused by the metallic fillings, and potentially inaccurate calculation on TPS due to streaking artifacts on CT images caused by metals. A number of previous studies have revealed the need for more accurate dose calculation techniques, such as Monte Carlo algorithm, especially when the structure is very close to the metallic implants and the local dose gradient is high, for example the abutting buccal or lingual mucosa as being studied here 14, 15, 16. Novel dose distributions generated by varying beam intensity and geometry within the IMRT software may explain the discrepancy in the trend of dose perturbations between this study and previous studies17, 18 most of which were done based on conventional RT techniques.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 We revealed the factor of the dose enhancement that was defined as the probability of electron generation. 9 They showed that the large errors were caused for the treatment planning without Monte Carlo calculation (MC). The backscatter around high-Z materials, that is dental implants, results in local dose enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Çatli reported that a high atomic number and density of dental implants led to major problems with regard to providing an accurate dose distribution in radiotherapy, and also with regard to contouring tumors caused by artifacts in head and neck tumors. 9 They showed that the large errors were caused for the treatment planning without Monte Carlo calculation (MC). The MC method is a good approach toward deriving the dose distribution in heterogeneous media.…”
Section: Introductionmentioning
confidence: 99%